The Effect of Agrosains Based Engineering Design Process Learning Model With A Stem Approach to SMP Student - Anjar Putro Utomo; Dyah Intan Prismasari; Erlia Narulita (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2021)
This research is aimed to study the effect of agroscience-based engineering design process learning model with STEM approach to junior high school student's HOTS. Research type is quasy-experiment with pre and post test control group design. This research done in even semester of 2019/2020 school year. Subject of this research is 7th grade students. Data collection technique and instrument in the form of test that covers revised Bloom Taxonomy HOTS indicator. Data analysis use kolmagorov smirnov normalization test, independent sample t-test and normalized gain. The result of independent sample t-test was Sig. (2-tailed) = 0.000 < sig. a = 0.05. Student's HOTS improvement in experiment class higher (N-gain= 0.494) than control class (N-gain=0.279). Base on result can be cloncuded that there is significant effect from agroscience-based engineerig design process learning model with stem approach to junior high school student's HOTS. Experiment class student's HOTS improvement category was middle.